PHENOLOGICAL OBSERVATIONS AND RESEARCH CONDUCTED ON THE AFRICAN MILLET PLANT - Mamashaeva Shokhsanam Rovshan qizi; Meyliev Akmal Kxushvaqtovich (European Journal of Agricultural and Rural Education, 2024)
In this article, the origin, distribution, nutritional value of African millet cultivated in Kashkadarya province, its importance for livestock, demand for external environmental factors, nutrient unit, protein content, spread of sucking pests found in African millet, sucker He gave information on the spread of harmful insects, the effect of entomophages on plant grain, and the conduct of chemical control work against sucking pests